The End of Innocence? - Meij, Dick van der (Studia Islamika, 2012)
This article is the review of Andrée Feillard and Rémy Madinier, The End of Innocence? Indonesian Islam and the Temptations of Radicalism. Singapore: NUS Press and IRASEC 2011, ISBN 978-9971-69-512-5The book discussed here is a successful attempt and provides a much more convincing multi-level description and understanding of the topic than has been the case so far. It looks at the combined political, cultural, historical and theological factors at play and explains that the heart of the matter is not Islam or Islamic religiosity per se but rather political structures and societal innovations within a framework of uncertain legal and global circumstances. The acute awareness of all players of the pivotal role of Islam in power games is acutely laid bare and the often unbelievable opportunist stance of all players dissected in gruesome detail. More research is however needed to provide more insight into the financial and organizational levels of the issue in the near future.DOI: 10.15408/sdi.v19i2.366